2020
DOI: 10.3389/fimmu.2020.01509
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Use of Exosomes in Sjögren’s Syndrome

Abstract: Sjögren’s syndrome (SS) is a chronic autoimmune disorder of the exocrine glands mediated by lymphocytic infiltrates damaging the body tissues and affecting the life quality of patients. Although traditional methods of diagnosis and treatment for SS are effective, in the time of personalized medicine, new biomarkers, and novel approaches are required for the detection and treatment of SS. Exosomes represent an emerging field in the discovery of biomarkers and the management of SS. Exosomes, a subtype of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 104 publications
0
32
0
Order By: Relevance
“…191 , 192 Multiple previously published reviews and research articles conclude that exosomes released from immune cells play both preventive and developmental roles in autoimmune diseases. 193 , 194 Mesenchymal stromal cell (MSC) exosomal immune properties are well studied. Zhang et al showed that MSC-derived exosomes induced production of CD4 + CD25 + Foxp3 + Treg or CD4 + CD25 + T-cells via allogeneic APC-enriched CD11C + cells through T-cell activation.…”
Section: Preclinical Research Developmentsmentioning
confidence: 99%
“…191 , 192 Multiple previously published reviews and research articles conclude that exosomes released from immune cells play both preventive and developmental roles in autoimmune diseases. 193 , 194 Mesenchymal stromal cell (MSC) exosomal immune properties are well studied. Zhang et al showed that MSC-derived exosomes induced production of CD4 + CD25 + Foxp3 + Treg or CD4 + CD25 + T-cells via allogeneic APC-enriched CD11C + cells through T-cell activation.…”
Section: Preclinical Research Developmentsmentioning
confidence: 99%
“…Immunologically active exosomes have been found to regulate innate and adaptive immune responses [165]. Thus, EVs can naturally be a part of the regimen for many ocular inflammatory conditions [166][167][168][169].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Sjögren’s syndrome is a chronic autoimmune disorder characterized by lymphocytic infiltration in the lacrimal and salivary glands, leading to eye and oral dryness. The exocrinopathy can result from primary Sjögren’s syndrome (pSS) or it can be secondary to other autoimmune disorders such as systemic lupus erythromatosus (SLE) or rheumatoid arthritis ( Huang et al, 2020 ). The pathogenesis of Sjögren’s syndrome involves activation of both innate and adaptive immune pathways, e.g., B cell-activating factor (BAFF)/BAFF receptor axis, interferon (IFN) signatures, and nuclear factor kappa B (NF-kB) signaling ( Sandhya et al, 2017 ).…”
Section: Exosomes In Ocular Surface Diseasesmentioning
confidence: 99%
“…The pathogenesis of Sjögren’s syndrome involves activation of both innate and adaptive immune pathways, e.g., B cell-activating factor (BAFF)/BAFF receptor axis, interferon (IFN) signatures, and nuclear factor kappa B (NF-kB) signaling ( Sandhya et al, 2017 ). Prognostic markers for Sjögren’s syndrome include anti-Ro/SSA, anti-La/SSB, and antinuclear autoantibodies (ANA) ( Huang et al, 2020 ). These autoantigens are released by salivary gland epithelial cells via exosomes.…”
Section: Exosomes In Ocular Surface Diseasesmentioning
confidence: 99%
See 1 more Smart Citation